Genetic modifiers of the Drosophila NSF mutant, comatose, include a temperature-sensitive paralytic allele of the calcium channel alpha1-subunit gene, cacophony. - Dellinger, B.; Felling, R.; Ordway, R.W. (Genetics, 2000)
The N-ethylmaleimide-sensitive fusion protein (NSF) has been implicated in vesicle trafficking in perhaps all eukaryotic cells. The Drosophila comatose (comt) gene encodes an NSF homolog, dNSF1. Our previous work with temperature-sensitive (TS) paralytic alleles of comt has revealed a function for dNSF1 at synapses, where it appears to prime synaptic vesicles for neurotransmitter release. To further examine the molecular basis of dNSF1 function and to broaden our analysis of synaptic transmission to other gene products, we have performed a genetic screen for mutations that interact with comt. Here we report the isolation and analysis of four mutations that modify TS paralysis in comt, including two intragenic modifiers (one enhancer and one suppressor) and two extragenic modifiers (both enhancers). The intragenic mutations will contribute to structure-function analysis of dNSF1 and the extragenic mutations identify gene products with related functions in synaptic transmission. Both extragenic enhancers result in TS behavioral phenotypes when separated from comt, and both map to loci not previously identified in screens for TS mutants. One of these mutations is a TS paralytic allele of the calcium channel alpha1-subunit gene, cacophony (cac). Analysis of synaptic function in these mutants alone and in combination will further define the in vivo functions and interactions of specific gene products in synaptic transmission.